The Impact of Artificial Intelligence on the Academic Performance of Pokhara University Business Students in Kathmandu - Khadka, Kripa (Nepalese Journal of Business, 2025)
This study examines the impact of artificial intelligence on the academic performance of Pokhara university business students in Kathmandu. Student academic performance (SAP) is the dependable variables. The independent variables are availability of alternatives resources, easy access to resources, time spent, personalized support and loss of creativity. The study is based on primary data with 142 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the impact of artificial intelligence on the academic performance of Pokhara university business students in Kathmandu. The study showed that availability of alternatives resources has a positive impact on student’s academic performance. It indicates that increase in availability of alternatives by artificial intelligence leads to increase the efficiency and enhance betterment on student’s academic performance. Likewise, easy access to resources has a positive impact on student’s academic performance. It indicates that increase in easy access to resources, leads to increase the efficiency of student’s academic performance. Similarly, time spent has a positive impact in student’s academic performance. It means that time spent leads to increase the efficiency of student’s academic performance. Moreover, personalized support has a positive impact on student’s academic performance. It indicates that increase in personalized support, leads to increase the student’s academic performance. In addition, loss of creativity has a positive impact in student’s academic performance. It reveals that increase in creativity, leads to increase the efficiency of student’s academic performance.